Optimality conditions for asymptotically stable control systems - Fernando Lobo Pereira (2007)
We consider an infinite horizon optimal impulsive control problems for which aperformance criteria is minimized by choosing asymptotically stable control strategies. Wepresent necessary optimality conditions in the form of a maximum principle and show howthey can be derived from an auxiliary conventional (nonimpulsive) optimal control problem.As far as we know, results of this kind have not been previously derived for problems withtrajectories restricted to the set of stabilizing ones.